INDONESIAN REGULATORY SYSTEM TOWARDS OWNERSHIP OF EXPLOSIVE DEVICES BY CIVILIANS - Dewantary, Zenny Rezania; Prisandani, Ulya Yasmine; Lardo, Mohammad Afdha (Faculty of Law, Parahyangan Catholic University, 2019)
Indonesia possessed laws and regulation concerning the acquisition, distribution and use of armed weapons and explosive devices. A number of incidents, however, show a faulty monitoring system. Terrorist groups involved in the Surabaya bombing this year has been known to use triaseton triperoxide also known as the mother of Satan (mos), commonly used by ISIS. This fact shows a weakness in the monitoring or supervisory system put in place to control the use of armed weapons and explosive devices. In this article, the author shall discuss, using a normative-empirical juridical approach, to what extent the prevailing national law has been synchronized with the existing international convention regulating the acquisition and use of armed weapons and explosive materials or devices.